2010
DOI: 10.1073/pnas.0911647107
|View full text |Cite|
|
Sign up to set email alerts
|

Unique multipotent cells in adult human mesenchymal cell populations

Abstract: We found adult human stem cells that can generate, from a single cell, cells with the characteristics of the three germ layers. The cells are stress-tolerant and can be isolated from cultured skin fibroblasts or bone marrow stromal cells, or directly from bone marrow aspirates. These cells can self-renew; form characteristic cell clusters in suspension culture that express a set of genes associated with pluripotency; and can differentiate into endodermal, ectodermal, and mesodermal cells both in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
689
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 449 publications
(762 citation statements)
references
References 25 publications
28
689
2
6
Order By: Relevance
“…During in vitro culture, hDSPCs, which exhibited stem celllike characteristics in our previous study, gradually lose the expression of transcription factors associated with multipotency and self-renewal, such as SOX2 and NANOG for maintaining the characteristics of stem cells. Several previous reports suggested that the quality of the stem cells strongly depend on the culture method (Driskell et al, 2012;Grayson et al, 2007;Kuroda et al, 2010;Minchenko et al, 1994;Reiter et al, 2008;Ren et al, 2006;Rendl et al, 2005). Thus, we investigated whether hDSPCs retain their stemness in various culture conditions despite long-term culture.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…During in vitro culture, hDSPCs, which exhibited stem celllike characteristics in our previous study, gradually lose the expression of transcription factors associated with multipotency and self-renewal, such as SOX2 and NANOG for maintaining the characteristics of stem cells. Several previous reports suggested that the quality of the stem cells strongly depend on the culture method (Driskell et al, 2012;Grayson et al, 2007;Kuroda et al, 2010;Minchenko et al, 1994;Reiter et al, 2008;Ren et al, 2006;Rendl et al, 2005). Thus, we investigated whether hDSPCs retain their stemness in various culture conditions despite long-term culture.…”
Section: Discussionmentioning
confidence: 92%
“…For suspension cultures, collagen type IV-enriched hDSPCs were plated in HydroCell plates (Nunc) with SKP medium (Biernaskie et al, 2009;Toma et al, 2001; or 2-hydroxyethyl methacrylate (poly-HEMA) as described previously (Kuroda et al, 2010). Briefly, 15 mg of poly-HEMA was dissolved in 1 ml of 95% ethanol by shaking at 37°C; the culture dish was coated with this solution and then air-dried on the clean bench overnight.…”
Section: Sphere Formation Of Hdspcsmentioning
confidence: 99%
“…Confluent cells were collected by 0.25% trypsin-EDTA, and were subjected for cell sorting to isolate Muse cells, as described previously. 8 In brief, cells were suspended in FACS Buffer, which contained 0.5% bovine serum albumin (BSA), 2 mM EDTA-2H 2 O in FluoroBrite DMEM (ThermoFisher Scientific, Japan) and were incubated with anti-human SSEA-3 antibody (1:400, BioLegend, Japan) for one hour on ice. Cells were then washed with FACS buffer for 3 times and centrifuged at 400 g for 5 min.…”
Section: Collection Of Muse Cellsmentioning
confidence: 99%
“…7 Previously, we identified unique stem cells that we named multilineage-differentiating stress enduring (Muse) cells as one to several percent of the total MSCs of the bone marrow, adipose tissue and dermis. 8 Among different cell populations in MSCs, Muse cells, which can be identified as cells positive for pluripotent surface marker SSEA-3, were initially found as stress tolerant cells, and show several aspects that may represent pluripotent-like differentiation ability of MSCs. 7,9 They are recognized to express pluripotent genes, able to differentiated into triploblastic cells from a single cells and are self-renewable, suggesting their pluripotency.…”
Section: Introductionmentioning
confidence: 99%
“…De telles cellules ont Ă©tĂ© dĂ©tectĂ©es dans le foie foetal, mais n'ont pas Ă©tĂ© rapportĂ©es dans la moelle osseuse. Reste l'hypothĂšse de la sĂ©lection de cellules mĂ©dul-laires pluri potentes dans des conditions particuliĂšres de contrĂŽle strict du degrĂ© de confluence, d'hypoxie, de sĂ©lection extensive d'un lot de sĂ©rum particulier, de conditions de stress telle une incubation prolongĂ©e dans une solution de trypsine [25,26]. De telles cellules pourraient ĂȘtre des vestiges de cellules souches embryonnaires ayant nichĂ© dans la moelle osseuse, ou pourraient rĂ©sulter d'une reprogrammation plus ou moins complĂšte selon un processus qui reproduirait in vivo l'induction in vitro des induced pluripotent cells.…”
Section: Les Csm/asc Sont-elles D'authentiques Cellules Souches ?unclassified